Effect of ultrasounds on neurons and microglia: Cell viability and automatic analysis of cell morphology. (September 2015) - Bocchi, Leonardo; Branca, Jacopo J.V.; Pacini, Stefania; Cosentino, Angela; Morucci, Gabriele; Ruggiero, Marco
Highlights: Neurons and microglial cells are treated with ultrasounds and differences in cell proliferation and morphology are evaluated in comparison to control untreated cells. Cell proliferation is evaluated by standard viability assay while cell morphology required the development of a special algorithm. Results showed that in ultrasound-treated cells, the number of elongations as well as their maximum length and their mean length were significantly increased in comparison to control untreated cells. Our data show that ultrasounds induce cell differentiation affecting cell morphology as well as the ability of neurons and microglia to form complex networks. Our results suggest the possibility of using ultrasounds to reconstitute neuronal and microglial circuits commonly altered in many neurodegenerative and neurodevelopmental disorders. Abstract: Ultrasounds, besides their well-established medical imaging role, influence the homeostasis of complex anatomical systems including the physiology of neurons and glia and the permeability of the blood brain barrier. In this study, neurons and microglial cells were treated with ultrasounds (commonly used in diagnostics) and differences in cell proliferation and morphology were evaluated in comparison to control, untreated cells. Cell proliferation was evaluated by standard viability assessment, while the quantitative analysis of cell morphology, usually performed by edge and line detection algorithms, required the development of a new special algorithm. In fact, traditional software methodologies do not provide the appropriate tools for morphological analysis of neurons and microglial cells, typically characterized by a roughly triangular body and numerous elongations of different lengths resulting in a complex neuron–microglia network. This new method, based on a modified Hough Transform algorithm using a matching operator instead of the common gradient filter, enabled the automatic identification of cell elongations and branches, the extraction of related information, and the comparison of the data between control and treated neurons, as well as microglial cells. Results, based on the development of the new algorithm, showed that in ultrasound-treated cells, the number of elongations, as well as their maximum and mean lengths, increased significantly in comparison to control, untreated cells. These results were consistent with the standard microscopic evaluation. Furthermore, a significant correlation between cell morphology and proliferation suggested that ultrasounds induced cell differentiation affecting cell morphology, as well as the ability of neurons and microglial cells to form complex networks. Our results suggest the possibility of using ultrasounds, currently utilized in diagnostics, to reconstitute neuronal and microglial circuits that are often altered in neurodegenerative and neurodevelopmental disorders.